Weak deflection angle of extended uncertainty principle (EUP) dirty black hole - Yu, Paul K. (Animo Repository, 2020)
This study calculates the correction due to the extended uncertainty principle (EUP) on the weak deflection angle of a Schwarzschild black hole surrounded by a dark matter halo of a finite thickness. The finite-distance form of Gauss-Bonnet theorem is applied to this dirty Schwarzschild blackhole with EUP quantum correction to determine the weak deflection angle. Results are compared with data of M87* supermassive black hole found by the Event Horizon Telescope to have a mass of ~109 solar masses. This fits within the criteria set by Mureika in Ref. [18], where the EUP quantum correction becomes relevant to dark matter effects when a black hole has a mass greater than or equal to 106 solar masses. Moreover, estimates in for the dark matter thickness revealed that both effects of dark matter and EUP cannot be detected using the realistic estimates for the dark matter halo size. This study hopes to provide deeper insights into the macroscopic effects of quantum gravity, particularly its role in the interplay between black holes and dark matter.